Cooking, Creativity, and Well‐Being: An Integration of Quantitative and Qualitative Methods. (15th June 2020) - Mosko, Jonathan E.; Delach, Madilynn J.
Abstract: This study seeks to uncover the benefits of participating in the act of cooking. The study was conducted in two phases at a mid‐sized private university on the East Coast: First was a phenomenological inquiry ( n  = 8), followed by a survey ( n  = 420). Measures included the Ryff scales of psychological well‐being and a survey of cooking attitudes and behaviors. Four distinct qualitative themes were identified in the first phase: cooking as a means of expressing creativity, positive attitudes about cooking, cooking as a valuable social opportunity, and cooking providing mood improvement. Cooking as a creative outlet was a key theme. We found small but significant correlations between frequency of cooking and the Ryff subscales of Environmental Mastery ( r  = .14, p  < .003), Positive Relationships with Others ( r  = .11, p  < .023), and Self‐Acceptance ( r  = .11, p  < .020). A Chi‐squared 2x1 analysis indicates that survey participants have a significant preference for cooking for themselves and others as opposed to only cooking for themselves. Results suggest that cooking as a creative intervention may contribute to the improvement of mood, social connections, and personal acceptance, and that cooking as a creative act may be relevant to individual well‐being.